The 5-minute face : the quick and easy makeup guide for every woman - Carmindy. frey50 (New York : Regan, 2007)
You're only five minutes away from your most beautiful face--and celebrity makeup guru Carmindy is here to show you how. The key isn't expensive cosmetics, complicated makeup regimens, or cluttering your bathroom counter with bottles and tubes--it's using the right products in the right places to enhance your own unique, natural beauty.--From publisher description.
Keywords: Beauty, Personal; Face -- Care and hygiene; Skin -- Care and hygiene; Cosmetics